Respiratory infections and chronic cough due to triple A (Allgrove) syndrome. Issue 3 (29th January 2020) - Zheng, Hengqi; Iyer, Ramesh S.; Pacheco, M. Cristina; Soares, Jennifer Jean; Johnson, Kaalan; Len, Mary; Ambartsumyan, Lusine
Abstract: Cough and respiratory infections are common in pediatrics. Our case report illustrates the need for pediatricians to consider rare diagnoses such as genetic syndromes and primary gastrointestinal motility disorders in patients with unremitting respiratory and gastrointestinal symptoms. Early identification provides early intervention and reduces long‐term morbidity for pediatric patients. Abstract : Cough and respiratory infections are common in pediatrics. Our case report illustrates the need for pediatricians to consider rare diagnoses such as genetic syndromes and primary gastrointestinal motility disorders in patients with unremitting respiratory and gastrointestinal symptoms. Early identification provides early intervention and reduces long‐term morbidity for pediatric patients.